Pengaruh Kedisiplinan dan Motivasi Kerja terhadap Kinerja Karyawan di PT Jasa Mandiri Utama - Hidajat, Koerniawan; Reza, Fakhrur (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Logistics has evolved along with increasing consumer behavior. A country's logistics performance is usually measured using the Logistics Performance Index (LPI). LPI is a tool for assessing the efficiency and sustainability of national or regional logistics systems. Indonesia still faces various challenges in the logistics sector. With the rapid growth of e-commerce and the need for fast delivery, the logistics industry in Indonesia is experiencing a significant transformation. This research aims to determine the influence of discipline and work motivation in the logistics sector on the performance of PT Jasa Mandiri Utama employees. Quantitative research methods. Primary data for respondent employees of PT. Main Mandiri Services via Google Form. Data analysis using SmartPLS software. The research results show that discipline has a positive effect on employee performance and work motivation has a positive effect on employee performance.